From intent to inertia: Experimental evidence from the retail electricity market - Christina Gravert (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2024)
I study consumers' choices in the retail electricity market. By conducting a largescale survey experiment with 3% of the Danish working-age population, I have gathered data on respondents' factual knowledge of the retail electricity market, their beliefs, preferences, and intentions to switch providers. Crucially, I can link their intentions with actual switching behaviors using nationwide smart meter data. My findings reveal a substantial gap between switching intentions and actions. This gap is exacerbated by my experimental interventions which 1) provide information about savings and switching costs and 2) decrease switching costs by offering free access to a switching service. While my interventions have large and significant effects on switching intention, they have only minor effects on actual switching behaviors. I calculate that a majority of consumers leaves money on the table by not switching. The low switching rates cannot be explained by biased beliefs or high switching costs. Demographics do not explain switching behavior, however, personality traits such as risk aversion, trust, and a tendency to avoid procrastination matter. The observed intention action gap can be explained by present-biased individuals who procrastinate and quickly forget to switch. Based on these findings, I suggest that simply drawing attention to information or educating consumers is unlikely to stimulate market activity. I recommend for policymakers to consider implementing smart defaults, for which I find strong citizen support in my research.
Keywords: C93; D03; D12; D83; L13; L43; L94; L98; 330; Consumer inertia; electricity markets; switching; field experiment